Withanolides with Phytotoxic Activity from Two Species of the Genus Salpichroa: S. origanifolia and S. tristis var. lehmannii - Nicotra, Viviana Estela (2013)
Seven new withanolides, salpichrolides O−U (1−7), the known 2,3-dihydrosalpichrolide B (9), a substance not previously isolated from a natural source, and three known compounds, salpichrolide D (8), salpichrolide A (10), and salpichrolide C (11), were isolated and characterized from the aerial parts of Salpichroa origanifolia and S. tristis var. lehmannii. Compounds 1−4 and 8 have an oxygenated D ring, while compounds 5−7 and 9−11 possess a six-membered aromatic D ring. The structures of the isolated compounds were identified by analysis of their spectroscopic data including NMR and MS. Withanolides 1, 3, 8, 10, and 11 exhibited selective radicle growth inhibition toward Lactuca sativa (lettuce) at 150 and 400 ppm.